Preventive Behaviors of Brucellosis in Khash City Ranchers Based on Health Belief Model - Madineh Shahnavazi; Masoudi Gholamreza; Alireza Ansari-Moghadam; Davood Raeisy; Fariba Varnamkhasti Khashei (Iranian Association of Health Education and Health Promotion, 2017)
Background and objective: Brucellosis is one of the most common zoonosis diseases more prevalent in Iran, especially in Sistan and Baluchestan Province, Iran. This study was aimed to assess factors influencing the behavior based on the Health Belief Model (HBM) among ranchers in Khash city, Iran. Materials and methods: In this cross-sectional study 200 rural ranchers of the Khash city were selected through randomized multistage sampling method from health centers. Data were collected through a researcher-made questionnaire with approved validity and reliability. In this study the role of awareness and health belief model constructs (perceived susceptibility, perceived severity, perceived benefits, perceived barriers and perceived self-efficacy) for the prognosis and implementation of rubella preventive behaviors were studied and analyzed. Data was analyzed using SPSS 18 and Pearson correlation coefficient for determining the relations of constructs and behaviors and linear regression test to determine the prediction of constructs on behavior. Results: The mean age of ranchers was 44±16; 53% of participants were male and 44.5% were illiterate. The mean age of knowledge of the participants was 33 ± 6.5. Between the knowledge, perceived susceptibility, perceived severity, perceived benefits and perceived self-efficacy and behavior there was a positive and significant association, but between the perceived barriers and behavior was a negative and significant association. Furthermore, results showed that self-efficacy and perceived benefits were the behaviors' predictors. Conclusion: Self-efficacy and perceived benefits were the strongest predictor of behavior. Educational programs based on the health belief model are recommended with an emphasis on increasing self-efficacy and perceived benefits to improve behavior. Paper Type: Research Article.